Global environmental change and planetary health in the curriculum of undergraduate health professionals in Latin America: a review. (April 2021) - Palmeiro-Silva, Yasna; Ferrada, Maria Teresa; Silva, Ignacio; Ramirez, Jorge
Abstract: Background: People living in Latin America are already affected by global environmental changes and several health inequities, increasing the risk of poor health. Health professionals have a key role in tackling these threats and their consequences by providing direct care and advocating for public health policies. Hence, health professionals should be taught about global environmental changes, climate change, and policy advocacy, which could be included under the planetary health frame. Unfortunately, whether these ideals have been included in the undergraduate curriculum in Latin American universities is unclear. We aimed to analyse the incorporation of courses on climate change, environmental health, and planetary health in the curriculum of undergraduate health professionals in Latin America. Methods: In this review, we did a documentary analysis of the curriculum of undergraduate health professional programmes that had been published on each university website. We selected the ten best Latin American universities for each country according to the QS Latin American University 2020, Times Higher Education World University 2020, and Academic Ranking of World Universities 2019 rankings. Between April 6 and May 5, 2020, we reviewed the curriculum of the nursing, medicine, nutrition, and psychology courses at these universities, looking for the phrases "climate change", "environmental health", and "planetary health" in the names of the courses offered. Findings: We included 161 universities and reviewed 392 courses. We identified 276 (70%) courses that incorporated public health or epidemiology, or both; however, only 118 (30%) courses covered environmental health, and only two (1%) courses were on climate change. None of the universities included in our review offered a planetary health course. Interpretation: Our findings imply that new Latin American health professionals are receiving insufficient training on environmental matters, which comprise roughly 25% of the global burden of disease. As we enter the Anthropocene epoch and rapid global environmental changes, health professionals need to be aware of the challenges and actively involved in the responses to protect the population and the environment. The planetary health approach facilitates this awareness and preparation. Planetary health education includes concepts regarding the holistic association between global environmental changes, natural systems, human health, and sustainability, among others, encompassing a broader perspective than just environmental health Funding: None.